Development of sustainable manufacturing decision making models for small and medium enterprises / Sujit Singh - Sujit, Singh (2016)

(untitled)
Sustainable manufacturing aims to manage the operations in an environmentally and socially responsible manner. Several organizations have already incorporated the concept of sustainable manufacturing. However, many Small and Medium Enterprises (SMEs) that account for approximately 90% of all enterprises are not yet embraced this opportunity. Therefore, it is important to develop the sustainable manufacturing decision making models that suited to the characteristics of manufacturing SMEs. In order to achieve that, this study aims to identify key sustainable manufacturing performance measures & metrics and develop the sustainability evaluation and strategy selection models. This study includes an empirical study to identify the key performance measures for sustainability assessment of manufacturing SMEs in an effective and comprehensive manner using the Triple Bottom-Line framework. In order to investigate the importance and applicability of the proposed measures and metrics, a survey was conducted among the practitioners. The result of Mann-Whitney U-test confirms that there is no significant difference between the importance and applicability of the proposed measures. Considering the human reasoning based decision-making in manufacturing SMEs,the development of decision-making models are based on the fuzzy set theory. This study also develops two sustainability performance evaluation models and one strategy selection model. For performance evaluation, the list of sustainability performance measures and metrics that is identified during the empirical study is applied. Consequently, a sensitivity analysis of the proposed method reveals the most important basic indicators affecting overall sustainability, identifying areas which decision makers should place special attention. For strategy selection model, the study develops a hierarchal multi-criteria decision making (MCDM) method by combining iv Analytical Hierarchal Process (AHP) and VlseKriterijuska Optimizacija I Komoromisno Resenje (VIKOR) methods under interval-valued fuzzy environment. The linguistic variables were expressed in the triangular interval-valued fuzzy sets. Using a case study of manufacturing SME, the final ranking of the strategies was elicited in accordance with this procedure. Subsequently, a sensitivity analysis was performed to validate the stability of the proposed final ranking. Apart from above mentioned studies, this study also includes the development of a fuzzy rule based expert system to provide an easy to access, time-saving and cost-effective way for sustainability evaluation and strategy selection. The expert system has two components: (1) sustainability evaluation and (2) strategy selection. The measures that are found important during sustainability evaluation process are considered as selection criteria for strategy selection. The applicability of the models and expert system were validated by implementation in manufacturing SMEs. This study contributes in several ways to the research field of sustainable manufacturing decision making. It provides a list of key performance measures and metrics for sustainability evaluation of manufacturing SMEs. In conjunction with the sustainability evaluation models and strategy selection model, this study assists the decision maker for improving their sustainability performances. An easy to access expert system provides a time saving, cost effective way for sustainable manufacturing decision making. The list of key performance measures & metrics, various modelling approaches and an expert system should also enrich the literature.